Effect of Patient Decision Aids in the Diagnosis and Treatment of Coronary Artery Disease：a Systematic Review - GAO Chuan, GAO Ying, ZHOU Yuyu, GUO Xufang, HE Zhong (Zhongguo quanke yixue, 2022)
BackgroundPatient decision aid is recognized as an essential tool for shared-decision making. However, it is not clear that its role in shared-decision making in the diagnosis and treatment of coronary artery disease (CAD) .ObjectiveTo assess the effect of patient decision aids in the diagnosis and treatment of CAD using a systematic review.MethodsDatabases of PubMed, Web of Science, EMBase and The Cochrane Library were searched from inception to March 2021 for randomized trials assessing the effect of patient decision aids used in the diagnosis and treatment of CAD patients using a type of searching algorithm consisting of subject headings and free words. The Cochrane risk-of-bias tool for randomized trials (RoB2) was used for assessing risk of bias. Data were extracted, and effects of patient decision aids were summarized.ResultsA total of six randomized trials were included, and their qualities were moderate on the whole. Four were published within the past five years; five were conducted in the United States; three focus on the treatment of CAD and another three are about chest pain assessment due to suspected CAD. The effects of patient decision aids were summarized as follows: (1) With the support of a patient decision aid, patients obtained changes in their decision-making behaviors (two studies) , increased CAD-related knowledge (all studies) , reduced decisional conflicts (three studies) , and higher rate of attending decision-making (two studies) . (2) Most of the patient decision aids are web-based, and their contents mainly include information related to CAD, clarifying the pros and cons of treatment schemes for CAD, and personal risk assessments.ConclusionThe effects of patient decision aids are limited in the diagnosis and treatment of CAD, yet they have broad prospect in clinical practice. To promote their application in China, it is suggested to strengthen relevant trainings for clinicians to develop patient decision aids in line with features of Chinese culture and patients.